2003
DOI: 10.1191/0267659103pf623oa
|View full text |Cite
|
Sign up to set email alerts
|

A review of anti-inflammatory strategies in cardiac surgery

Abstract: It is generally accepted that cardiac surgery is frequently associated with the development of systemic inflammatory response. This phenomenon is very variable clinically, and can be detected by measuring plasma concentrations of certain inflammatory markers. Complement component, cytokines and adhesion molecules are examples of these markers. Systemic inflammation can be potentially damaging to major organs. Several anti-inflammatory strategies have been used in recent years, aiming to attenuate the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Several anti-inflammatory procedures and pharmacological agents have been used in cardiac surgery to attenuate myocardial inflammatory injury, including the use of leukocyte filtration, corticosteroids, aprotinin, heparin, and nitrogen monoxidum donor compounds [32]. Despite the relatively small number of studies investigating the effects of reducing the inflammatory response on myocardial injury, the vast majority of these studies have shown that therapies targeting myocardial inflammatory response are beneficial in salvaging myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Several anti-inflammatory procedures and pharmacological agents have been used in cardiac surgery to attenuate myocardial inflammatory injury, including the use of leukocyte filtration, corticosteroids, aprotinin, heparin, and nitrogen monoxidum donor compounds [32]. Despite the relatively small number of studies investigating the effects of reducing the inflammatory response on myocardial injury, the vast majority of these studies have shown that therapies targeting myocardial inflammatory response are beneficial in salvaging myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Most Patients undergoing cardiac surgical procedures with CPB have SIRS [15-17] The antioxidant and anti-inflammatory effects of PTX have been showed in many studies [18,19]. PTX has also been reported to exhibit anticoagulation properties by improving red blood cell deformability, decreasing red blood cell aggregation, and inhibiting neutrophil adhesion [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several anti‐inflammatory techniques and pharmacological agents (largely aimed at coping with CPB) have been used in recent years in cardiac surgery. These include leukocyte filtration, corticosteroids, aprotinin, heparin and NO donor compounds ( Harig et al , 2001 ; Paparella et al , 2002 ; Asimakopoulos and Gourlay, 2003 ; Goudeau et al , 2007 ). Despite the relatively small number of studies investigating the effects of reducing the inflammatory response on myocardial reperfusion injury, majority of these studies have shown evidence of myocardial protection.…”
Section: Cardioprotective Strategies During Open‐heart Surgerymentioning
confidence: 99%